POST-INTENSIVE CARE DEPRESSION FOLLOWING CRITICAL ILLNESS IN PATIENTS AFTER USING MECHANICAL VENTILATION - Faizatuz Azzahrah Syamsudi; Bambang Pujo Semedi; Betty Agustina Tambunan (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: Critical illness survivors have been improved due to advances in critical medicine, but they can experience psychological impairments after ICU discharge. Depression is one of the psychological impairments in Post-Intensive Care Syndrome (PICS). Post-Intensive Care Syndrome is a collection of symptoms that occur post-ICU discharge. This can be experienced by post-intensive care patient after using mechanical ventilation. Post-intensive care depression has an impact on the patient quality of life after ICU discharge. Objectives: This study aimed to determine post-intensive care depression in patients after using mechanical ventilation and to investigate correlation duration of mechanical ventilation and ICU length of stay with post-intensive care depression. Methods: This study was an observational analytic study with a cross-sectional design and retrospective medical record. We used total sampling technique. We enrolled all post-intensive care patient after using mechanical ventilation at Gedung Bedah Pusat Terpadu Dr. Soetomo General Hospital in a range of January-December 2020. The number of samples in this study was 97 Patients. We collect detailed sociodemographic data and clinical data from medical record. The symptoms of post-intensive care depression were assessed at least 3 months after ICU discharge with Beck Depression Inventory-II (BDI-II). The data were analyzed using Chi-Square statistical test. Results: Out of 97 post-intensive care patients after using mechanical ventilation, 43 patients fulfilled the inclusion criteria and 27.91% among them had mild depression (BDI-II score = 14-19). There is no significant correlation between post-intensive care depression and duration of mechanical ventilation (p-value = 0.398) and there is no significant correlation between post-intensive care depression and ICU length of stay (p-value = 0.303). Conclusion: Post-intensive care patients after using mechanical ventilation are prone to have mild depression at least three months after ICU discharge. However, there is no significant correlation duration of mechanical ventilation and ICU length of stay with post-intensive care depression.